Dispersion of grain refiner particles in molten aluminium - Asbjornsson, Einar Jon (2001)
Nine types of Al-Ti, Al-Ti-C and Al-Ti-B master alloy rods have been investigated by metallography and also by LiMCA measurements after the dissolution of the alloys in an aluminium melt. The results show the presence of TiC and TiB2 particle clusters in the Al-Ti-C and Al Ti-B alloys, respectively. The size of the clusters as measured by LiMCA was in the range of 20-100µm.The percentage of the total TiB2 and TiC additions to the melt that was found in the clusters was up to 2.8%. EDX analysis of the TiC particle clusters showed the presence of oxygen, presumably in the form of aluminium oxide, and the TiB2 clusters also contained oxygen, fluorine and potassium. AI-5Ti-1B master alloys from different manufacturers contain different quantities of impurities containing oxide and fluoride salts. Furthermore, the distribution of phases varies, especially with respect to texturing of the TiB2 particles, and the impurities show a varying degree of association with the TiB2 texture lines. The Al-Ti-C master alloys also showed texturing but the main difference was observed in their oxide content. The quantity of clusters as determined by LiMCA can be related to the microstructure of the master alloys, further supporting the conclusion that oxide plays an important role in cluster formation in the Al-Ti-C rods and the impurities containing oxide and fluoride salts in the Al-Ti-B rods. The LiMCA tests also confirm that further agglomeration of the clusters and particles occurs in the aluminium melt both for Al-Ti-C and AI-Ti-B master alloys. The flow conditions and particle distribution in an aluminium melt in launders was modelled using CFD for two launder designs. In the first design the effect of vortex formation in the dead-zone at a corner of the launder was demonstrated. Particle dispersion from a point source simulating the dissolution of a master alloy rod was modelled for the second launder. An effective distribution was achieved within 1000 mm from the source of particle introduction, this distance being less than that required for the dissolution of the soluble TiAl3 particles from the master alloys. LiMCA measurements in the first launder and chemical analysis of samples taken from the flowing melt support the flow and particle distribution modelling.